Green hypocrisy? Environmental attitudes and residential space heating expenditure - Laura Traynor; Ian A. Lange; Mirko Moro (Center for Economic Studies and ifo Institute (CESifo), 2012)
In the UK, the largest proportion of household energy use is for space heating. Popular media make claims of a green hypocrisy: groups which have the strongest attitude towards the environment have the highest emissions. This study examines whether environmental attitudes and behaviours are associated with space heating energy use using data from the British Household Panel Survey. Results find that environmentally friendly attitudes generally do not lead to lower heating expenditures though environmentally friendly behaviours are associated with lower heating expenditure. Also, the effect of these attitudes and behaviours do not change as income increase.
Keywords: Q40; Q50; 330; green hypocrisy; heating expenditures; environmental attitudes; BHPS; Umweltbewusstsein; Wärmeenergie; Verbraucherausgaben; Energiekonsum; Großbritannien